On the road with the Erasmus IP Wisdom Project - improving an on-line business by applying Web Mining Techniques - Seruca, Isabel (2020)
The Web can be regarded as the largest database available and presents a challenging task for efficient design and access. Web mining aims at the discovery and analysis of useful information from the Web through the use of data mining techniques. In this paper we report our experiences in applying web mining techniques to an e-business platform of a retail company. The company related Web content data and its usage are analyzed with data mining tools. The underlying idea will be to address web marketing purposes, suggesting improvements for both the on-line business and the website. The work here reported was developed in the context of an Erasmus Intensive Programme (IP) project.